An anti-secularist pan-Asianist from Europe: Paul Richard in Japan, 1916-1920 - Krämer, Hans Martin (Modern Asian studies, 2023)
The modern Japanese nation-state that was established from 1868 onwards was marked by a strong tendency towards the separation of state and religion: religions were protected as a private matter, but the public sphere was resolutely kept free of them. This was mainly done so that competing religions would not get in the way of state-sanctioned emperor worship. The latter, although imbued with elements from Shinto, was carefully defined as non-religious, so that emperor worship could be prescribed without harm to the constitutionally guaranteed freedom of religion. This secularist approach to policing religions was broadly shared among Japanese elites—but it did not remain unopposed. - From around the turn of the twentieth century, dissatisfaction with the separation of the religious and the secular spheres began to be voiced, especially by pan-Asianist activists, who sought to combine the spiritual unity of Asia with the political liberation of Asian countries from Western colonialism and imperialism. Although Japanese pan-Asianism has conventionally been seen as a purely political movement, one cannot explain it fully without taking into account its spiritual dimension, which up to the 1920s drew its primary inspiration from India. This article will show how pan-Asianist activists in Japan opposed mainstream secularism and discuss what their vision for a unified Asia was. In doing so, it will focus on the Japanese reception of the Frenchman Paul Richard, an important political activist-cum-spiritual seeker who was a central node in the network of Indian and Japanese pan-Asianists in the early twentieth century.